The Struggle Against Global Terrorism as an Expression of a Clash Between Civilisat ions - NAGAR, Nir Barkan (Przegląd Strategiczny, 2018)
The struggle against global terrorism is taking place, and it is between civilizations. It is a war against radical international terror, which is attempting to change the world order and is sowing fear among both citizens and governments. Huntington maintains that people can re define their identity and consequently the boundaries and compositions of civilizations change. The phenomenon of the ‘Islamic State’ illustrates this. There is a cultural difference between civilizations that support Islamic terror, which tramples individual rights, and Western civilizations that are dedicated to pluralism and democracy. The Western world for already seven decades has been under attack by international terrorism, and the peak is the phenomenon of the ‘Islamic State’, which began in the Middle East and now is attacking Europe, and not just Europe. A difficult global war is being waged, and it is necessary to find an effective response to the threat. This response will include a multi-system strategy that addresses ideology, media, financing, and operational activity, including the handling of European residents who joined the ranks of the Islamic State and acquired operational experience, returned to Europe, and constitute an infrastructure of terrorism and terrorist attacks. The integration of forces and resources, significant operational activity, and legislative changes that curtail individual liberties, in cooperation with the moderate Muslim population, will enable the West and Europe to defeat the terrorist entities that trample in all ways the fundamental values of humanity and human life.